OVERVIEW OF FORMULATION, MANUFACTURE AND APPLICATIONS OF MINI TABLETS - PATIL, PRATIKSHA; P., RASHMI (International Journal of Current Pharmaceutical Research, 2020)
Mini tablets, recent trend of solid dosage form, made remarkable contribution to avoid certain obstacles in people’s mind and offered best therapeutic benefits, flexible dose and combined released pattern. Mini tablets were developed and reported as patient friendly with increased patient acceptance. Mini tablets were made into modified release system for better dose and prolong drug release. They offer the advantage of reduced dose dumping and increased effect of drug by localization. Manufacture of mini tablets are similar to conventional tablets but need a change in tooling, equipment and specifications. Evaluation parameters found to be similar with conventional tablets but doses are variable. Mini tablets can also be encapsulated and hence different drug combinations are tried and found useful.